(488) Lecture Notes on Operations Research-Linear Programming ملاحظات المحاضرة حول بحوث العمليات - البرمجة الخطية (معهد التخطيط القومي, 2026)
تتناول المبادئ الأساسية لـ "بحوث العمليات" مع تركيز خاص على "البرمجة الخطية" كأداة رياضية لاتخاذ القرارات الرشيدة في ظل محدودية الموارد ، يستعرض البحث التطور التاريخي لهذا العلم منذ استخدامه في الأغراض العسكرية خلال الحرب العالمية الثانية، وصولاً إلى تطبيقاته الواسعة في مجالات الإدارة والاقتصاد والصناعة، موضحاً الخصائص الجوهرية لبحوث العمليات مثل "التوجه النظامي" والاعتماد على فرق العمل متعددة التخصصات لحل المشكلات المعقدة من خلال بناء نماذج رياضية دقيقة ،ويفصل الملف أنواع مشكلات القرار التي تعالجها بحوث العمليات، مثل مشكلات المخازن، والتوزيع، والانتظار، والإحلال، مع تقديم شرح معمق لتقنيات "البرمجة الخطية" وطرق تمثيلها رياضياً وبيانياً ، كما يستعرض البحث نماذج تطبيقية شهيرة مثل "مشكلة الغذاء" و"مشكلة النقل" و"تخطيط الإنتاج"، موضحاً كيفية استخدام خوارزميات متطورة مثل "طريقة السمبلكس" للوصول إلى الحلول المثلى التي تحقق أقصى ربح أو أدنى تكلفة، مما يجعل المذكرة مرجعاً علمياً يربط بين النظرية الرياضية والتطبيقات العملية في إدارة المؤسسات . The basic principles of "Operations Research" are addressed, with a special focus on "Linear Programming" as a mathematical tool for making rational decisions under limited resources. The research reviews the historical development of this science from its use for military purposes during World War II to its wide applications in the fields of management, economics, and industry. It explains the essential characteristics of Operations Research, such as "systematics orientation" and reliance on multidisciplinary work teams to solve complex problems by building accurate mathematical models. The document details the types of decision problems that Operations Research addresses, such as warehouse, distribution, waiting, and replacement problems, while providing an in-depth explanation of "Linear Programming" techniques and methods of representing them mathematically and graphically. The research also reviews famous applied models such as the "Food Problem," the "Transport Problem," and "Production Planning," explaining how to use advanced algorithms such as the "Simplex Method" to reach optimal solutions that achieve maximum profit or minimum cost, making the document a scientific reference that links mathematical theory and practical applications in the management of institutions.